Angiotensin-Converting Enzyme Inhibitors and the Risk of Congenital Malformations. Issue 1 (January 2017) - Bateman, Brian T.; Patorno, Elisabetta; Desai, Rishi J.; Seely, Ellen W.; Mogun, Helen; Dejene, Sara Z.; Fischer, Michael A.; Friedman, Alexander M.; Hernandez-Diaz, Sonia; Huybrechts, Krista F.
Abstract : OBJECTIVE: To examine the association between first-trimester angiotensin-converting enzyme (ACE) inhibitor exposure and the risk of overall major congenital, cardiac, and central nervous system malformations. METHODS: We used a cohort of completed pregnancies linked to liveborn neonates derived from Medicaid claims from 2000 to 2010. We examined the risk of malformations associated with first-trimester exposure to an ACE inhibitor. Propensity score–based methods were used to control for potential confounders including maternal demographics, medical conditions, exposure to other medications, and measures of health care utilization. RESULTS: The cohort included 1, 333, 624 pregnancies, of which 4, 107 (0.31%) were exposed to ACE inhibitors during the first trimester. The prevalence of overall malformations in the ACE inhibitor–exposed pregnancies was 5.9% compared with 3.3% in the unexposed (unadjusted relative risk, 1.82; 95% confidence interval [CI] 1.61–2.06), of cardiac malformations was 3.4% compared with 1.2% (relative risk 2.95, 95% CI 2.50–3.47), and of central nervous system malformations was 0.27% compared with 0.18% (relative risk 1.46, 95% CI 0.81–2.64). After restricting the cohort to pregnancies complicated by chronic hypertension (both exposed and unexposed) and accounting for other confounding factors, there was no significant increase in the risk of any of the outcomes assessed. Relative risks associated with first-trimester ACE inhibitor exposure were 0.89 (95% CI 0.75–1.06) for overall malformations, 0.95 (95% CI 0.75–1.21) for cardiac malformations, and 0.54 (95% CI 0.26–1.11) for CNS malformations. CONCLUSIONS: After accounting for confounders, among women with hypertension, exposure to ACE inhibitors during the first trimester was not associated with an increased risk of major congenital malformations. Abstract : Supplemental Digital Content is Available in the Text.After accounting for confounders, particularly hypertension and diabetes, angiotensin-converting enzyme inhibitor exposure during the first trimester is not associated with an increased risk of malformations.